Preparation method and application of high-strength, ultraviolet-blocking and slow-release fertilizer degradable agricultural mulching film

Agricultural mulch films prepared using PVA, sodium lignosulfonate, and nanocellulose have solved the problems of traditional mulch films being non-degradable, having low strength, and lacking UV blocking and fertilizer slow-release properties. They achieve high strength, UV blocking, and fertilizer slow-release effects, thus promoting sustainable agricultural development.

CN120904608APending Publication Date: 2025-11-07JILIN AGRI SCI & TECH COLLEGE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511123573.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-12
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing agricultural mulch films have problems such as being non-degradable, having low strength, lacking ultraviolet blocking and fertilizer slow-release functions, leading to soil pollution, low fertilizer utilization, and affecting crop growth.

Method used

Using polyvinyl alcohol (PVA), sodium lignosulfonate, nanocellulose, and fertilizer as raw materials, a high-strength, UV-blocking, and slow-release fertilizer biodegradable agricultural mulch film is prepared through a specific process. The interaction between nanocellulose and sodium lignosulfonate improves the mechanical and degradation properties of the mulch film, and the slow release of fertilizer is achieved through the slow degradation of the mulch film.

Benefits of technology

Mulch film has high tensile strength, good UV blocking properties and slow-release fertilizer characteristics, which can extend its service life, reduce soil pollution, improve fertilizer utilization and promote crop growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120904608A_ABST
    Figure CN120904608A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of agricultural materials, in particular to a preparation method and application of a high-strength, ultraviolet-blocking and slow-release fertilizer degradable agricultural mulching film, polyvinyl alcohol, sodium lignin sulfonate, nanocellulose and a fertilizer are used as raw materials and mixed according to a specific proportion, and the agricultural mulching film is prepared through the steps of nanocellulose extraction, solution preparation, mixing and drying and the like. The tensile strength of the mulching film is larger than or equal to 51.28 MPa, the elongation at break is larger than or equal to 251.97%, the ultraviolet transmittance is smaller than or equal to 1.16%, the 60-day degradation rate is larger than or equal to 63.53%, and the mulching film has the functions of water retention, heat preservation, ultraviolet blocking and fertilizer slow release, can slowly release fertilizer in the crop growing season and can be degraded into soil fertilizer after harvesting. The preparation method is simple, wide in raw material source, low in cost and suitable for soil covering in agricultural planting, the problems of pollution, insufficient performance and the like of a traditional mulching film are solved, and agricultural sustainable development is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of agricultural materials, in particular to a preparation method and application of a high-strength, ultraviolet-blocking and slow-release fertilizer degradable agricultural mulching film. BACKGROUND

[0002] Soil is an important basis for crop growth, not only supplying water and nutrients, but also inhibiting pathogens. However, with the decline of soil fertility, the problem of nutrient loss is becoming increasingly serious, further exacerbating the decline in crop yield. Agricultural mulching film helps to conserve water and heat by covering the soil, which is an effective means to alleviate this problem. The widely used petroleum-based plastic mulch has caused serious "white pollution" due to its difficulty in degradation, and has insufficient functions in mechanical properties, ultraviolet resistance and fertilizer slow release. Although ultraviolet light has a certain sterilization effect, its excessive irradiation may cause crop dwarfing, leaf yellowing and weakened photosynthesis, ultimately affecting yield. Therefore, the development of a new type of agricultural mulching film with biodegradability and improved mechanical properties, ultraviolet protection and fertilizer slow release functions is a key direction to achieve sustainable agricultural development and environmental protection.

[0003] Existing degradable mulching films are all based on chemical or natural polymers, organic-inorganic composite materials, and are prepared by adding plasticizers, crosslinking agents and fertilizers. Polyvinyl alcohol (PVA) is widely concerned in many fields such as agricultural mulching film production due to its excellent biocompatibility and biodegradability. This material is widely used in biological medicine, film packaging, soil improvement, flexible sensors and other fields. However, in a humid environment, PVA film is prone to absorb water in the air, leading to material swelling and mechanical property degradation. Due to the presence of a large number of hydrophilic hydroxyl groups in the molecular chain, this defect limits the application of the material in certain environments. However, the addition of plasticizers and crosslinking agents may slow down the degradation rate of the mulch, therefore, the use of PVA as a mulch material also requires the addition of other natural fiber materials to enhance its mechanical properties and reduce its hydrophilicity.

[0004] Currently, it is common to add some plasticizers, crosslinking agents or plasticizers to improve the performance of polyvinyl alcohol (PVA). For example, the invention patent CN115746576B discloses a green and environmentally friendly agricultural mulching film preparation method, which improves the mechanical properties of PVA by adding bamboo powder, plasticizer and crosslinking agent. The invention patent CN120158021A discloses a preparation method of degradable mulching film, which improves the mechanical tensile properties of the mulch by adding modified polyvinyl alcohol (PVA), modified starch and plasticizer. The invention patent CN115926347B discloses a preparation method and application of a slow-release fertilizer biodegradable mulch, which improves the mechanical properties of PVA mulch and the slow-release function of fertilizer by adding lignin, plasticizer and fertilizer.

[0005] The preparation method of the green and environmentally friendly agricultural mulching film disclosed in invention patent CN115746576B improves the mechanical properties of the PVA mulching film by adding a crosslinking agent and a plasticizer, but the effect is still small, and the tensile properties are not better and stronger, and the improvement effect is not significant. At the same time, the prepared mulching film does not have the functions of fertilizer slow release and ultraviolet radiation resistance. The preparation method of the degradable mulching film disclosed in invention patent CN120158021A can improve the mechanical tensile properties and fertilizer slow release function of the mulching film by adding modified polyvinyl alcohol (PVA), modified starch and plasticizer, but the tensile strength is still relatively low. At the same time, the mulching film does not have the function of ultraviolet radiation resistance, and the degradation of the mulching film is less than 40% in 50 days, and the degradation speed is slow. The preparation method of the biodegradable mulching film with slow-release fertilizer disclosed in invention patent CN115926347B improves the tensile strength and elongation at break of the mulching film, but the improvement is not significant. At the same time, the mulching film does not have the function of ultraviolet radiation resistance.

[0006] However, traditional polyethylene mulching film is difficult to degrade, and long-term use can cause soil compaction, environmental pollution and other problems. In addition, some existing degradable mulching films have the problems of insufficient strength and poor weather resistance, and are easily damaged in the field, affecting the use effect. At the same time, the traditional mulching film cannot realize the slow-release function of the fertilizer, which leads to low fertilizer utilization rate and increased environmental pollution risk. In addition, ultraviolet radiation can accelerate the aging of the mulching film and shorten its service life, therefore, developing an agricultural mulching film with high strength, ultraviolet blocking, slow-release fertilizer and degradable characteristics has become a research hotspot in the agricultural field. SUMMARY

[0007] In view of the deficiencies in the prior art, the present application provides a high-strength, ultraviolet-blocking and slow-release fertilizer degradable agricultural mulching film to solve the problems of non-degradable, low strength, lack of ultraviolet blocking and slow-release fertilizer function of traditional mulching film.

[0008] The technical scheme adopted by the present application to solve its technical problems is: a high-strength, ultraviolet-blocking and slow-release fertilizer degradable agricultural mulching film is prepared from polyvinyl alcohol (PVA), sodium lignosulfonate, nanocellulose and fertilizer, and the amount of each raw material is: 10-30 parts by mass of sodium lignosulfonate, 3-20 parts by mass of nanocellulose solution, and 2-10 parts by mass of fertilizer relative to 100 parts by mass of PVA.

[0009] Further, the nanocellulose is derived from corn straw or corn husk and is prepared by a specific process, which gives the mulching film good mechanical properties and degradation properties.

[0010] Further, the fertilizer is one or a combination of urea, phosphate fertilizer, potassium fertilizer, and trace element fertilizer, and the type and ratio of the fertilizer can be adjusted according to the requirements of different crops.

[0011] Further, the agricultural mulching film has a tensile strength of greater than or equal to 51.28 MPa, an elongation at break of greater than or equal to 251.97%, a transmittance of less than or equal to 1.16% in the ultraviolet band of 200-400 nm, and a degradation rate of greater than or equal to 63.53% in 60 days, and has the characteristics of high strength, ultraviolet blocking, degradability, and fertilizer release.

[0012] Preparation method A preparation method of the agricultural mulching film, comprising the following steps: Nano-cellulose extraction and preparation: corn bract or corn straw is ground into powder, which is passed through a 90-mesh sieve, and then the powder is placed in a 5% sodium hydroxide solution and magnetically stirred at 85°C for 3h, and then filtered, washed, and dried, and then mixed with maleic anhydride and reacted in an oven at 120°C for 4h, and then washed and filtered after the reaction is completed, and then a cellulose solution with a mass fraction of 0.5% is prepared, and then ultrasonic crushing is performed on the cellulose solution for 30 minutes at a power of 300-500W to obtain a nano-cellulose solution.

[0013] PVA solution preparation: PVA powder is dissolved in water and heated and stirred until completely dissolved to obtain a PVA solution.

[0014] Cellulose-enhanced PVA solution preparation: the nano-cellulose solution is added to the PVA solution and stirred uniformly to obtain a cellulose-enhanced PVA solution.

[0015] Mixed solution preparation: the cellulose-enhanced PVA solution is uniformly stirred with sodium lignosulfonate to obtain a cellulose-enhanced PVA / sodium lignosulfonate solution.

[0016] Mulching film forming: the fertilizer is added to the mixed solution, uniformly stirred, and then poured into a mold, and then natural drying or constant-temperature drying is performed to obtain the agricultural mulching film.

[0017] Advantages of the present application: The agricultural mulching film of the present application uses PVA as a matrix, combines sodium lignosulfonate and nano-cellulose, significantly improves the tensile strength and elongation at break of the mulching film through intermolecular interaction and network structure formation, and makes the mulching film not easy to break during field use, thereby prolonging the service life.

[0018] The addition of nano-cellulose and sodium lignosulfonate endows the mulching film with good ultraviolet blocking performance, effectively reduces the aging effect of ultraviolet light on the mulching film, and reduces the adverse effects of ultraviolet light on the soil and crops.

[0019] The fertilizer is evenly dispersed in the mulch film, and the slow degradation of the mulch film realizes the slow release of the fertilizer, improves the fertilizer utilization rate, reduces the loss of the fertilizer and environmental pollution, and simultaneously continuously provides nutrients according to the growth cycle of crops.

[0020] The mulch film is made of degradable materials, can be gradually degraded in a natural environment, and has a degradation rate of 63.53% or more in 60 days, avoids the soil pollution problem caused by traditional mulch films, and meets the environmental protection requirements.

[0021] The preparation method is simple, the raw materials are widely available, and the cost is low, so that the method is suitable for large-scale industrial production. BRIEF DESCRIPTION OF DRAWINGS

[0022] The application is further described below in combination with the drawings and examples.

[0023] Figure 1 is the actual morphology and various deformability of the mulch film of Example 3; Figure 2 is the water vapor transmission rate of the mulch film of Comparative Example 1, the mulch film of Comparative Example 2, and the PSCU of Examples 1-4; Figure 3 is the mechanical property test result of the mulch film of Comparative Example 1, the mulch film of Comparative Example 2, and the PSCU of Examples 1-4; Figure 4 is the tensile cycle test of the PSCU of Example 3; Figure 5 is the ultraviolet radiation resistance test result of the mulch film of Comparative Example 1, the mulch film of Comparative Example 2, and the PSCU of Examples 1-4; Figure 6 is the ultraviolet-visible light transmittance test result of the mulch film of Comparative Example 1, the mulch film of Comparative Example 2, and the PSCU of Examples 1-4; Figure 7 is the fertilizer slow-release test result of the mulch film of Comparative Example 1, the mulch film of Comparative Example 2, and the PSCU of Examples 1-4; Figure 8 is a comparison chart of the degradation rates of the mulch film of Comparative Example 1, the mulch film of Comparative Example 2, and the PSCU of Examples 1-4; Figure 9 is a real picture of the germination and growth of small cabbage seeds covered by the mulch film of Example 3, a blank control, and an LDPE mulch film; Figure 10 is a comparison chart of the germination rates of small cabbage seeds covered by the mulch film of Example 3, a blank control, and an LDPE mulch film; Figure 11 is a comparison chart of the growth heights of small cabbages covered by the mulch film of Example 3, a blank control, and an LDPE mulch film; Figure 12 is a comparison chart of the fresh weights and dry weights of small cabbages covered by the mulch film of Example 3, a blank control, and an LDPE mulch film. DETAILED DESCRIPTION

[0024] In order to make the technical means, creative features, purposes and effects of the present application easy to understand, the present application is further described below in conjunction with specific embodiments.

[0025] The preparation method of the high-strength, ultraviolet-blocking and slow-release fertilizer degradable agricultural mulch described in this embodiment includes the following steps: Step 1: Nanocellulose extraction and preparation: corn bract or corn straw is ground into powder, which is passed through a 90-mesh screen. The powder is placed in a 5% sodium hydroxide solution and magnetically stirred at 85°C for 3h. After filtration, washing and drying, it is mixed with maleic anhydride and reacted in a 120°C oven for 4h. After the reaction is completed, it is washed, filtered, and configured into a 0.5% cellulose solution. After ultrasonic crushing for 30 minutes, a nanocellulose solution is obtained. Step 2: Add the nanocellulose solution to the PVA solution and stir until uniform to obtain a cellulose-enhanced polyvinyl alcohol solution. Step 3: Stir the solution obtained in step 2 with sodium lignosulfonate until uniform to obtain a cellulose-enhanced polyvinyl alcohol / sodium lignosulfonate solution. Step 4: Add fertilizer to the mixed solution obtained in step 3, stir until uniform, and then pour into a mold and dry to obtain the agricultural mulch.

[0026] Example 1

[0027] A preparation method of a high-strength, ultraviolet-blocking and slow-release fertilizer degradable agricultural mulch includes the following steps: (1) Nanocellulose extraction: corn bract powder is passed through a 90-mesh screen, placed in a 5% sodium hydroxide solution and magnetically stirred at 85°C for 3h. After filtration, washing and drying, it is mixed with maleic anhydride and reacted in a 120°C oven for 4h. After the reaction is completed, it is washed, filtered, and configured into a 0.5% nanocellulose solution. After ultrasonic crushing for 30 minutes, a nanocellulose solution is obtained.

[0028] (2) Mix 24ml of water with 3ml of the above nanocellulose solution and stir until uniform. Add 3g of PVA powder, heat and stir for 2h until dissolved to obtain a PVA / nanocellulose mixed solution.

[0029] (3) Add 0.3g (10 parts by mass relative to 100 parts by mass of PVA) of sodium lignosulfonate powder to the solution of step (2) and stir until uniform.

[0030] (4) Add 0.06g (2 parts by mass relative to 100 parts by mass of PVA) of urea, stir until uniform, and then pour into a mold. Dry at 60°C for 24h to obtain PSCU1 mulch.

[0031] Example 2

[0032] A method for preparing a high-strength, ultraviolet-blocking, and slow-release fertilizer degradable agricultural mulch, in step (2), 21 ml of water and 6 ml of nanocellulose solution are taken, in step (3), 0.6 g (20 parts by mass relative to 100 parts by mass of PVA) of sodium lignosulfonate is added, in step (4), 0.15 g (5 parts by mass relative to 100 parts by mass of PVA) of a mixture of urea and phosphate fertilizer is added, and other steps are the same as in Example 1 to obtain PSCU2 mulch.

[0033] Example 3

[0034] A method for preparing a high-strength, ultraviolet-blocking, and slow-release fertilizer degradable agricultural mulch, in step (2), 21 ml of water and 6 ml of nanocellulose solution are taken, in step (3), 0.6 g (20 parts by mass relative to 100 parts by mass of PVA) of sodium lignosulfonate is added, in step (4), 0.15 g (5 parts by mass relative to 100 parts by mass of PVA) of a mixture of urea and phosphate fertilizer is added, and other steps are the same as in Example 1 to obtain PSCU2 mulch.

[0035] Example 4

[0036] A method for preparing a high-strength, ultraviolet-blocking, and slow-release fertilizer degradable agricultural mulch, in step (2), 21 ml of water and 6 ml of nanocellulose solution are taken, in step (3), 0.6 g (20 parts by mass relative to 100 parts by mass of PVA) of sodium lignosulfonate is added, in step (4), 0.15 g (5 parts by mass relative to 100 parts by mass of PVA) of a mixture of urea and phosphate fertilizer is added, and other steps are the same as in Example 1 to obtain PSCU2 mulch.

[0037] Comparative Example 1 A method for preparing a mulch, without adding nanocellulose, and other steps are the same as in Example 1 to obtain PSU mulch.

[0038] Comparative Example 2 A method for preparing a mulch, only 3 g of PVA powder is dissolved in 27 ml of water, without adding sodium lignosulfonate, nanocellulose, and fertilizer, and a pure PVA mulch is obtained after drying.

[0039] Example 5 Mulch Performance Test Experiment Example 5.1 Water Vapor Transmission Experiment Water vapor transmission experiments are performed on the mulch of Comparative Example 1, Comparative Example 2, and Examples 1-4, and the results of the water vapor transmission experiments are shown in Table 1. Figure 2 Figure 2 From the experimental data, it can be concluded that the water vapor transmission of Examples 1-4 does not exceed 500 g / (m 2 ​• 24h), conforming to the requirements of GB / T35795-2017. When the volume of nanocellulose solution is 9ml, PSCU has a minimum water vapor permeability of 311.23g / (m³). 2 • 24h), at which point the cross-linking between nanocellulose and PVA is most dense and has the best strength. As the amount of nanocellulose solution increases, the water vapor permeation of PSCU decreases, but when the amount of nanocellulose solution is 18ml, the water vapor permeation of PSCU increases. It is speculated that this is because the cross-linking strength between nanocellulose solution and PVA is weak, and the nanocellulose solution agglomerates and is unevenly dispersed, leading to an increase in water vapor permeation.

[0040] Example 5.2 Mechanical Property Experiment Mechanical performance tests were conducted using the plastic film from Comparative Example 1 and Comparative Example 2, and the PSCU from Examples 1-4. The results of the mechanical performance tests are as follows: Figure 3 As shown. Analysis Figure 3 It can be verified that adding nanocellulose can enhance the mechanical properties of the mulch film. As the amount of nanocellulose gradually increases, the tensile strength and elongation at break of the PSCU mulch film first increase and then decrease, indicating that an appropriate amount of nanocellulose increases the tensile properties of the film. Figure 3 It can be verified that the longitudinal tensile elongation at break of the PSCUF of this invention is >150%, which meets the requirements of GB / T35795-2017. Further analysis of the PSCU in Examples 1-4 in the figure confirms that when the amount of nanocellulose is 9ml, the mechanical properties of the mulch film are optimal, with tensile strength and elongation at break reaching 52.35MPa and 256.69%, respectively. This is three times higher than the tensile strength of 17.06MPa disclosed in patent CN115926347B. Figure 4 For Example 3, the film was subjected to tensile cycling at 120% strain. After 15 cycles, the film did not break, demonstrating good fatigue resistance.

[0041] Example 5.3 UV radiation resistance test The UV resistance performance was tested using the mulch films of Comparative Example 1 and Comparative Example 2, and the PSCUs of Examples 1-4. The mulch films were irradiated with UV lamps for 1 minute, and the colors of the UV-sensitive cards were compared after the films were removed. The results of the UV resistance performance test are as follows: Figure 5 As shown. By Figure 5 It can be verified that the pure PVA mulch film in Comparative Example 1 has no function in resisting ultraviolet radiation; ultraviolet rays can completely penetrate the mulch film and reach the ultraviolet sensing card. Comparative Example 2 and Examples 1-4, which contain sodium lignosulfonate, all have the function of resisting ultraviolet radiation and can block ultraviolet rays from penetrating the mulch film. Figure 6The data represent the ultraviolet transmittance of Comparative Example 1, Comparative Example 2 mulch films, and PSCU mulch films of Examples 1-4 in the 200-800 nm wavelength range. 200-400 nm is considered the ultraviolet radiation band. Figure 6 It can be verified that the average transmittance of Comparative Example 2 in the 200-400nm band is 87.06%, while the average transmittance of the mulch film with added sodium lignosulfonate in the sub-band is only 1.16%, which is almost non-transmittable to ultraviolet rays, so it has the function of ultraviolet protection.

[0042] Example 5.4 Experiment on fertilizer release through plastic film Soil fertilizer release experiments were conducted using the plastic film in Comparative Example 1 and PSCU in Examples 1-4. The results of the soil release experiments are as follows: Figure 7 As shown, the blank control group for this experiment was... Figure 7 In the Urea group, pure urea granules were released into the soil. Analysis verified that, compared to the blank control and Comparative Example 1, the PSCU of this invention exhibited superior slow-release fertilizer performance in the soil. Analysis also verified that the release of urea from the PSCU in Examples 1-4 was significantly slower in the soil than in Comparative Example 1 and the blank control group, indicating that the fertilizer release behavior of the PSCU of this invention can be controlled by adjusting the amount of nanocellulose used in the mulch film.

[0043] Example 5.5 Experiment on the degradation performance of plastic film Degradation performance experiments were conducted using the mulch film of Comparative Example 1, Comparative Example 2, and PSCU of Examples 1-4. The blank control group was a traditional low-density polyethylene mulch film (LDPE). The results of the degradation performance experiments are as follows: Figure 8 As shown. There are Figure 8 It can be seen that the degradation rate of traditional polyethylene mulch film is 0% within 60 days, meaning no degradation occurs. In contrast, the degradation rate of PSCU in Examples 1-4 is 63.53%–73.78% within 60 days, while the degradation rates of Comparative Examples 1 and 2 are 35.79%–47.27% within 60 days, demonstrating faster degradation performance compared to traditional polyethylene mulch film. The higher degradation rate of PSCU in Examples 1-4 ensures that even if some mulch film remains after crop harvest, it can be incorporated into the soil through tilling and continue to degrade until complete degradation. Furthermore, the mulch film with added fertilizer can fertilize the soil after degradation, increasing soil fertility and benefiting the next crop planting.

[0044] Example 5.6 Plant Germination Experiment Using the plastic film (as described in Example 3), a blank control (without plastic film), and traditional polyethylene plastic film, a germination experiment of Chinese cabbage seeds was conducted in flowerpots. The experiment lasted for 14 days, with 25 Chinese cabbage seeds placed in each group. The germination rate and growth process of the Chinese cabbage seeds in different groups were observed and tracked over 14 days. The actual germination and growth of the Chinese cabbage seeds in different groups are shown below. Figure 9 As shown. ByFigure 9 It can be seen that the sprouting and growth trend of the pakchoi seeds covered by the mulch of Example 3 is obviously better than that of the blank control group and that of the pakchoi seeds covered by the traditional polyethylene mulch, which shows that the PSCU mulch has the fertilizer slow-release effect and helps the better growth of crops.

[0045] Figure 10 The sprouting rate of the pakchoi seeds in each stage of different groups was analyzed Figure 10 It can be verified that the sprouting rate of the pakchoi seeds covered by the mulch of Example 3 is 84% at 14 days, which is obviously higher than 60% of the blank group and 80% of the LDPE group.

[0046] Figure 11 For the growth height of the pakchoi at 14 days, the average growth height of the pakchoi covered by the mulch of Example 3 is 6.65 cm, which has obvious advantages compared with 5.08 cm of the blank group and 5.7 cm of the LDPE group, which shows that the mulch of the application indeed has the fertilizer slow-release effect and promotes the growth of crops.

[0047] Similarly Figure 12 For the fresh weight and dry weight of the pakchoi at 14 days, the fresh weight and dry weight of the pakchoi covered by the mulch of Example 3 are higher than those of the LDPE group and the blank group. Figure 12 It can be verified that the fresh weight and dry weight of the pakchoi covered by the mulch of Example 3 are higher than those of the LDPE group and the blank group. Figure 12 It is further proved that the growth performance of the pakchoi sample covered by the PSCU mulch of the application is better.

[0048] The above shows and describes the basic principles, main features and advantages of the application. It should be understood by those skilled in the art that the application is not limited by the above examples, and the above embodiments and descriptions in the specification are only to illustrate the principles of the application, and various changes and improvements can be made to the application without departing from the spirit and scope of the application, and these changes and improvements all fall within the scope of the application. The scope of protection of the application is defined by the appended claims and their equivalents.

Claims

1. A high-strength, ultraviolet-blocking and slow-release fertilizer degradable agricultural mulching film, characterized in that, The agricultural mulching film is prepared from polyvinyl alcohol, sodium lignosulfonate, nanocellulose and fertilizer, wherein the amount of each raw material is as follows: 10-30 parts by mass of sodium lignosulfonate, 3-20 parts by mass of nanocellulose solution and 2-10 parts by mass of fertilizer, relative to 100 parts by mass of polyvinyl alcohol.

2. The high-strength, ultraviolet-blocking and slow-release fertilizer degradable agricultural mulching film according to claim 1, characterized in that: The nanocellulose is derived from corn stalks or corn husks.

3. The high-strength, ultraviolet-blocking and slow-release fertilizer degradable agricultural mulching film according to claim 1, characterized in that: The fertilizer is one or a combination of urea, phosphate fertilizer, potassium fertilizer and trace element fertilizer.

4. The high-strength, ultraviolet-blocking and slow-release fertilizer degradable agricultural mulching film according to claim 1, characterized in that: The tensile strength of the agricultural mulching film is ≥51.28 MPa, the elongation at break is ≥251.97%, the transmittance in the ultraviolet band of 200-400 nm is ≤1.16%, and the degradation rate in 60 days is ≥63.53%.

5. The method for preparing the high-strength, ultraviolet-blocking, and slow-release fertilizer degradable agricultural mulching film according to any one of claims 1-4, characterized in that, The method comprises the following steps: Step 1: nanocellulose extraction and preparation: corn husks or corn stalks are ground into powder, which is passed through a 90-mesh sieve, and then the powder is placed in a 5% sodium hydroxide solution and stirred magnetically at 85°C for 3 hours. After filtration, washing and drying, the powder is mixed with maleic anhydride and reacted in an oven at 120°C for 4 hours. After the reaction is completed, the product is washed, filtered and configured into a cellulose solution with a mass fraction of 0.5%. The solution is then ultrasonically pulverized for 30 minutes to obtain a nanocellulose solution; Step 2: the nanocellulose solution is added to the PVA solution and stirred uniformly to obtain a cellulose-reinforced polyvinyl alcohol solution; Step 3: the solution obtained in Step 2 is stirred uniformly with sodium lignosulfonate to obtain a cellulose-reinforced polyvinyl alcohol / sodium lignosulfonate solution; Step 4: the fertilizer is added to the mixed solution obtained in Step 3, which is stirred uniformly and then poured into a mold and dried to obtain the agricultural mulching film.

6. The method for preparing a high-strength, ultraviolet-blocking, and slow-release fertilizer degradable agricultural mulching film according to claim 5, characterized in that: The preparation method of the polyvinyl alcohol solution in Step 2 is as follows: polyvinyl alcohol powder is dissolved in water and heated and stirred until completely dissolved.

7. The method for preparing a high-strength, UV-blocking, and slow-release fertilizer biodegradable agricultural mulch film according to claim 5, characterized in that: The drying in Step 4 is natural drying or constant-temperature drying.

8. The method for preparing a high-strength, ultraviolet-blocking, and slow-release fertilizer degradable agricultural mulching film according to claim 5, characterized in that: The power of the ultrasonic pulverization in Step 1 is 300-500 W.

9. Use of the mulch film according to any one of claims 1 to 4 in agricultural cultivation, characterized in that, The agricultural mulching film is used for soil covering, achieving water and heat preservation, ultraviolet blocking and slow-release of fertilizer.

10. The use of the agricultural mulching film according to claim 9 in agricultural planting, characterized in that, The agricultural mulching film slowly releases fertilizer during the crop growth season and can be degraded into soil fertilizer after harvesting.

Citation Information

Patent Citations

  • A green and environmentally friendly agricultural mulch film and preparation method thereof

    CN115746576B

  • A biodegradable mulch film for slow-release fertilizer and its preparation method and application

    CN115926347B

  • Modified degradable mulching film as well as preparation method and application thereof

    CN120158021A